Graphic and Multimedia Design to Promote Tourism for Ranong Province - Waijittragum, Pibool (Asian Creative Architecture, Art and Design, 2022)
The idea of this research is to explore the identity of Ranong province. to increase economic competitiveness towards sustainable development through graphic and multimedia design. The objectives were 1) to study the identity of Ranong Province from natural resources and cultural bases, 2) to study the tourism resources of Ranong Province, 3) to design brand property, multimedia and interactive media to promote tourism in Ranong Province. Research methodology applied using qualitative research methods with field surveys and interviews with business owners. And also using quantitative research methods with questionnaire for the targets. The research results consist of 1) brand identity of Ranong Province, 2) tourism souvenirs of Ranong Province, and 3) interactive media of Ranong Province tourism routes, all 3 issues are based on natural resources and culture. Representation with the story of a multicultural city and contemporary characteristics. The design process uses an illustration to imply the story. Characteristic of all design consist of the look of natural, vernacular, and contemporary.